Impact of PharmaNet-Based Admission Medication Reconciliation on Best Possible Medication Histories for Warfarin - Au, Debbie (Can J Hosp Pharm, 2016)
BACKGROUND: Inaccurate documentation of medication histories may lead to medication discrepancies during hospital admissions. Obtaining a best possible medication history (BPMH) for warfarin can be challenging because of frequent dosage changes and nonspecific directions of use (e.g., “take as directed”). On February 27, 2012, the study hospital implemented an admission medication reconciliation (MedRec) process using a form that compiled the most recent 6 months of outpatient prescription dispensing history from a provincial electronic database called PharmaNet. It was unclear whether admission MedRec had improved the process of obtaining warfarin BPMHs and the quality of their documentation. OBJECTIVE: To compare the rates of complete warfarin BPMH documentation before and after implementation of PharmaNet-based admission MedRec. METHODS: A single-centre, retrospective chart review was conducted using the health records of patients receiving warfarin who were admitted to the hospital’s Internal Medicine service before and after implementation of admission MedRec. The study periods were October 1, 2009, to February 26, 2012, and February 27, 2012, to July 31, 2014, respectively. The primary outcome was the rate of complete warfarin BPMH documentation during each period. RESULTS: Data were recorded for 100 patients in the pre-implementation phase and 100 patients in the post-implementation phase. The rates of complete warfarin BPMH documentation were 65% and 84% in these 2 phases, respectively (p = 0.002). CONCLUSION: Implementation of PharmaNet-based admission MedRec was associated with a statistically significant increase in the rate of complete warfarin BPMH documentation.